2003
DOI: 10.1046/j.1467-2494.2003.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐stage kinetic analysis of fragrance evaporation and absorption from skin

Abstract: Human in vivo fragrance evaporation data from a previously published study are reanalysed in terms of compartmental pharmacokinetic models in which the microscopic rate constants are functions of the physicochemical properties of the fragrance components. According to the proposed analysis, which is restricted to low doses, absorption and evaporation of each component are first-order processes occurring from either the skin (one-compartment model) or the skin and a more rapidly depleted vehicle layer (two-comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…This is supported by another experimental study, in which was shown that skin penetration of HICC was enhanced under occlusion by a factor of >3 (27). In comparison, evaporation from other, unoccluded sites may go along with a lesser sensitization or elicitation risk (28, 29).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by another experimental study, in which was shown that skin penetration of HICC was enhanced under occlusion by a factor of >3 (27). In comparison, evaporation from other, unoccluded sites may go along with a lesser sensitization or elicitation risk (28, 29).…”
Section: Discussionmentioning
confidence: 99%
“…Musks are responsible for bringing sensuality and warmth to a fragrance [1], as well as adding their excellent fixative properties [2,3]. Presently, natural products extraction involves high costs and generates small amounts of raw material, so synthetic odorants are greatly demanded.…”
Section: Theories Regarding Odor Prediction and Recognitionmentioning
confidence: 99%
“…where the difference established between experimental and theoretical values was plotted (for both GGA/PW91 and B3LYP results), as shown in (2). In such equation, for a certain mode , the difference (DIFF) is obtained through the subtraction of its theoretical value (TheoWavenumber) from its experimental value (ExpWavenumber).…”
Section: Partmentioning
confidence: 99%
“…The major components reflect the biological properties of essential oils, but their activity, for example the cell penetration, hydrophobicity and fixation on membranes, can be modulated by the minor components (Bakkali et al, 2008;. The composition of CEO results in interactions between the components that both qualitatively and quantitatively change their evaporation rates (Saiyasombati and Kasting, 2003).…”
Section: Factors Affecting the Antimicrobial Effect Of Essential Oilsmentioning
confidence: 99%
“…A parallel effect is the evaporation of the components of essential oils, which occurs more rapidly at higher temperatures. It is known that the antimicrobial effects of essential oils decrease over time-in a matter of hours-due to evaporation (Droby et al, 2008;Inouye et al, 2003;Saiyasombati and Kasting, 2003).…”
Section: Factors Affecting the Antimicrobial Effect Of Essential Oilsmentioning
confidence: 99%